SEKOLAH GRATIS, SEKOLAH TAK BERDAYA - B. P. Sitepu (Perspektif Ilmu Pendidikan, 2006)
In the compulsory basic education program, the Government implements a set of policies, one of which is providing funds directly to schools through Block Grant or Operational Fund Assistance. This policy is expected to strengthen school capability in managing and developing school activities to improve the instructional quality and to give more opportunity for school age children to attend schools. Based on the observation at two government primary schools in Jakarta, it is found out that the policy has weakened the school creativity due to the strict regulations and supervision on the usage of the fund provided by the Government. The educational activities previuosly developed and funded under school initiatives have to be terminated as in the present regulation the schools are not allowed to find financial resources, while the fund provided by the Government is not enough to support the activities. The school master will have serious sanctions if he/she does not follow the regulations properly. This study suggests the existing regulations should be reviewed and improved.